2017
DOI: 10.3892/etm.2017.4880
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of burdock leaves on elastase and tyrosinase activity

Abstract: Abstract. Burdock (Arctium lappa L.) leaves generate a considerable amount of waste following burdock root harvest in Taiwan. To increase the use of burdock leaves, the present study investigated the optimal methods for producing burdock leaf extract (BLE) with high antioxidant polyphenolic content, including drying methods and solvent extraction concentration. In addition, the elastase and tyrosinase inhibitory activity of BLE was examined. Burdock leaves were dried by four methods: Shadow drying, oven drying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…The results showed a potent antioxidant and lipid peroxidation inhibitory effects comparable to tocopherol and suggested that the plant could be considered as a medicinal source for the treatment and prevention of many free radical diseases (Shahriari et al, 2007). Plant extract with antioxidant polyphenols can inhibit elastase activity, which can be explained through ROS scavenging theory of skin aging (Horng et al, 2017). Our result shows higher elastase inhibitory activity in rose petals compared to receptacle which is in line with higher ABTS scavenging activity as antioxidant parameter.…”
Section: Antielastase Assaysupporting
confidence: 72%
“…The results showed a potent antioxidant and lipid peroxidation inhibitory effects comparable to tocopherol and suggested that the plant could be considered as a medicinal source for the treatment and prevention of many free radical diseases (Shahriari et al, 2007). Plant extract with antioxidant polyphenols can inhibit elastase activity, which can be explained through ROS scavenging theory of skin aging (Horng et al, 2017). Our result shows higher elastase inhibitory activity in rose petals compared to receptacle which is in line with higher ABTS scavenging activity as antioxidant parameter.…”
Section: Antielastase Assaysupporting
confidence: 72%
“…In fact, the accretion of free radicals induced by UV exposure can provoke skin problems via a series of cell destruction mechanisms [20]. These dermatological disturbances, including skin elasticity decrease and hyperpigmentation, were reported to be clinically correlated with ROS [21]. Therefore, the discovery of ABTS free radical scavengers MA and MB could be useful for the prospective development of anti-skin aging drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Solar radiation, or UV radiation, is the major stimulator that accelerates the overproduction of reactive oxygen species (ROS) which leads the endogenous oxidative stress in the epidermis (Kim et al 2016). Moreover, the excess oxidative stress is so harmful that it induces unhealthy and aging skin contributing as wrinkle, roughness, dryness, elasticity loss, and uneven pigmentation due to the degradation of extracellular matrix (ECM) (Horng et al 2017). In addition, the exalted levels of ROS can cause not only the senescence and damage of biological functions such as lipid membrane peroxidation, DNA deterioration, cell death but also human's disease, namely, cancer, stroke, Parkinson's disease, heart disease, arteriosclerosis, infection, and autoimmune disease (Popoola et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Collagen is the most abundant protein structure in the human dermis layer providing the tensile strength of the skin; meanwhile, elastin, a fiber network located in the connective tissue, is responsible for the elastic recoil property. Indeed, collagen and elastin are necessary to the skin which play major role for the plumpness, flexibility, integrity, and elasticity keeping skin youthful and healthy (Horng et al 2017;Siedle et al 2002;Thring et al 2009;Varani et al 1998). However, the accumulated ROS after skin exposure to photoaging stressors can indirectly activate dermal enzymes such as collagenase and elastase which basically break down and degrade collagen as well as elastin, respectively (Chatatikun and Chiabchalard 2017; Popoola et al 2015; Sahasrabudhe and Deodhar 2010).…”
Section: Introductionmentioning
confidence: 99%